Editorial (2020)
The July-December 2020 issue of the IUSTA Journal expounds on themes where the protagonist is the State, in order to reflect on its role in fields such as the Colombian penitentiary system, the territory from the perspective of the indigenous communities of the Sierra Nevada de Santa Marta, and the provision of medical services.